(untitled) (Medico Legal Update, 2020)
Introduction – Female deaths, especially young married females always arouse suspicions, but later age females who have crossed 30 years of age are not the cases which draws our attention. So, we conducted an observational study for a period of 1 year in autopsy of SSG Hospital, Baroda. Material & Method – Of all cases coming for the postmortem examination, cases in which the victim is married female and above 30 years of age were taken for the study when there was suspicion regarding the cause of death. Results – Victims having Illiterates (16.66 %), primary (45.83 %), secondary (33.33 %) school education were total 95.82 % of cases. It was observed that 72.91 % of deaths were suicidal in nature followed by accidental (22.91 %) and homicidal deaths (4.16 %). Statistical analysis –The data collected was analyzed using MS Excel worksheets for averages and percentage. Conclusion – Education holds a very pivotal role in the prevention of unnatural deaths in females.